Migracja zarobkowa jako problem społeczny = Job migration as a social problem - based on selected literature - Bochno, Ireneusz (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper attempts to examine the social problem of job migration among young Poles. It includes the definition of the concept, the situation of young people under the current circumstances, as well as the consequences of job migration of Polish people.
Keywords: migracja; mobilność zawodowa